Structure and properties of solid state materials (Alpha Science International, 2006)
This book structure and properties of solid state materials covers mainly the designing aspects of materials, based on the requisite properties and applications. This book also includes some aspects of modern materials especially that of carbon nano-materials, materials for energy storage applications and catalytic,...